Pelatihan Teknik Inventarisasi Hutan untuk Mewujudkan Kemandirian Pengelolaan Hutan Rakyat di Bogor - Qori Pebrial Ilham; Muhdin Muhdin; Priyanto Priyanto; Sri Rahaju; Nining Puspaningsih (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Private forest farmers in Karyasari Village typically sell standing trees using a "borongan" system without knowing the actual stand volume, while buyers rely on visual estimation methods. This situation is attributed to the lack of a standardized reference for estimating timber volume in private forests. This community service program aimed to transform the farmers' paradigm regarding timber selling systems towards measurable volume-based estimation through technical training on forest inventory. The program involved 30 members of the Kelompok Wanita Tani Sipon Harum Lestari and Kelompok Tani Harapan Maju in Karyasari Village, Bogor Regency. The training employed an andragogical approach, encompassing material dissemination, demonstrations of simple measurement tools, field practice, and training evaluation. The effectiveness of the training was assessed using a one-group pre-test and post-test design. Paired t-test analysis revealed a significant increase in knowledge regarding tree dimension measurement (p=0.0001) and volume estimation (p=0.0037). These findings indicate that the training on forest inventory techniques successfully enhanced the farmers' capacity to measure tree dimensions and estimate timber volume. This knowledge is highly valuable as a benchmark for establishing an independent and sustainable private forest timber selling system.